Inducing Defects in (19)F-Nanocrystals Provides Paramagnetic-free Relaxation Enhancement for Improved In Vivo Hotspot MRI - Mashiach, Reut (Nano Lett, 2020)
[Image: see text] Paramagnetic relaxation enhancement (PRE) is the current strategy of choice for enhancing magnetic resonance imaging (MRI) contrast and for accelerating MRI acquisition schemes. Yet, debates regarding lanthanides’ biocompatibility and PRE-effect on MRI signal quantification have raised the need for alternative strategies for relaxation enhancement. Herein, we show an approach for shortening the spin–lattice relaxation time (T(1)) of fluoride-based nanocrystals (NCs) that are used for in vivo (19)F-MRI, by inducing crystal defects in their solid-crystal core. By utilizing a phosphate-based rather than a carboxylate-based capping ligand for the synthesis of CaF(2) NCs, we were able to induce grain boundary defects in the NC lattice. The obtained defects led to a 10-fold shorter T(1) of the NCs’ fluorides. Such paramagnetic-free relaxation enhancement of CaF(2) NCs, gained without affecting either their size or their colloidal characteristics, improved 4-fold the obtained (19)F-MRI signal-to-noise ratio, allowing their use, in vivo, with enhanced hotspot MRI sensitivity.